"Jogar, encontrar os amigos ou espalhar o currículo por aí : uma etnografia na lan house e no telecentro - Carvalho, Olivia Bandeira de Melo (2010)
Based on an ethnographic research in a lan house - a public and paid center for internet and computer access and a telecentro a public center for free internet and computer access located in Morro do Estado, a community of low income in Niterói city (RJ), this work discusses the different types of technological appropriation in each of these spaces, frequented mainly by young people, and discuss the concept of digital inclusion , used in political speeches as a way of promoting social inclusion. The participant observation indicates points of analysis which might not be revealed by a survey that did not allow the perception of the subjects involved. The uses and meanings the young people, other residents of the community and policy makers attach to the lan house and the telecentro reveal categories which are not limited to a discussion of digital inclusion . The work also presents a discussion on identity and community, on the importance of leisure and sociability, as well as on projects constructed by young people, within their field of possibilities in relation to information technology and communication.